Wind energy handbook - Burton, Tony, 1947- (Wiley, 2011)
"Fully revised and updated, now covering offshore wind turbines, this is a comprehensive description of the mechanical, electrical, aerodynamic, meteorological and planning aspects of modern wind turbines. Fully revised and updated, this second edition addresses key developments in the wind technology since the first edition, now the leading reference on the subject, was published in 2001. A completely new chapter focuses on offshore wind turbines and wind farms. After a brief introduction, the authors discuss the wind resource. Particular reference is made to wind turbulence due to its importance in wind turbine design. A discussion on the basis of the aerodynamics of horizontal axis wind turbines follows, incorporating general momentum theory and dynamic stall, and an analysis of their performance. The book goes on to assess the requirements for establishing design loads, updating national and international standards and revising dynamic analysis codes where necessary. Burton et al. also set out the various design options for horizontal axis wind turbines, discussing variable speed operation and reviewing alternative blade materials and their properties. They explain the functions of the wind turbine controller and describe some of the possible analysis techniques. The text also reviews the development of wind energy projects with particular emphasis on environmental impact, and considers how wind turbines interact with the electrical power system. The 1st edition is the leading reference for wind energy researchers and practitioners worldwide. This edition has 25% new material, including a new chapter covering offshore wind turbines and wind farms. Revises the chapter on the aerodynamics of horizontal axis wind turbines to include new sections on general momentum theory, lifting line theory and dynamic stall. Comprehensively covers advances in wind turbine technology, featuring updated chapters on wind resource, design and design loads, and reviews wind farms and the development of wind energy projects. Provides data on Standards and National Targets on a companion website."--